Evaluation of Pseudomonas fluorescens , beltanol and some Resistances Inducers for control of Melon Wilt Caused by Fusarium oxysporum f.sp. melonis - N. Alhamiri, Yaser; Gh. Abdulmohsen, Raja; jaefar, Ola H.; A. Khdem, Ali (Journal of Kerbala for Agricultural Sciences, 2018)
The objective of the study was to evaluate the effectiveness of Pseudomonas fluorescens and some of the Inducers agents in the control of fusarium wilt disease on melon plants caused by Fusarium oxysporum f.sp.melonis. The study also tested the pathogenicity of pathogenic fungi isolates and compared the efficacy of bacteria and induction agents using Beltanol agents to control this disease. The results of the Fusarium oxysporum f.sp.melonis test showed that FOM8 isolates were the most isolated using the seeds of the cabbage. The rate of seed germination rate was reduced to 0.00% compared to the control treatment with a germination rate of 100%. Pure isolation of Pseudomonas fluorescens was obtained. The test of the antibiotic susceptibility of these bacteria showed that it has a high resistance against pathogenic fungi. Pseudomonas fluorescens inhibited the growth of Fusarium oxysporum f.sp.melonis on the PSA by 92%. While the results of the antibiotic test EM1 and herbal extraction Ascophyllum nodosum against the isolation of fungus Fusarium oxysporum f. sp. Melonis in the PSA has achieved an inhibition rate of 88% and 82%, respectively. When Fusarium oxysporum f.sp.melonis was performed under the field conditions, Results also showed that Pseudomonas fluorescens and induction factors reduced the severity of the disease to 6% compared to the treatment of pathogenic fungi only, which reached 44% severity, and showed a significant increase in the rate of soft weight and total length The length of the plant was 45.3 cm after 45 days compared to the control treatment (pathogen only) which was 18.6 while the soft weight of the vegetative and root group was 12.8 g compared with the treatment of the pathogen only, which amounted to 5.3 g.